Slab-Triggered Arc Flare-up in the Cretaceous Median Batholith and the Growth of Lower Arc Crust, Fiordland, New Zealand. (24th July 2017) - Decker, M.; Schwartz, J. J.; Stowell, H. H.; Klepeis, K. A.; Tulloch, A. J.; Kitajima, K.; Valley, J. W.; Kylander-Clark, A. R. C.
Abstract: The Mesozoic continental arc in Fiordland, New Zealand, records a c. 110 Myr history of episodic, subduction-related magmatism that culminated in a terminal surge of mafic to intermediate, high-Sr/Y, calc-alkalic to alkali-calcic magmas. During this brief, 10–15 Myr event, more than 90% of the Cretaceous plutonic arc root was emplaced; however, the source of these rocks and the degree to which they represent lower crustal mafic and/or metasedimentary recycling versus the addition of new lower arc crust remain uncertain. We report whole-rock geochemistry and zircon trace element, O-isotope and Hf-isotope analyses from 18 samples emplaced into lower arc crust (30–60 km depth) of the Median Batholith with the goals of (1) evaluating the processes that triggered the Cretaceous arc flare-up event and (2) determining the extent to which the Cretaceous arc flare-up resulted in net addition of lower arc crust. We find that δ 18 O (Zrn) values from the Western Fiordland Orthogneiss range from 5·2 to 6·3‰ and yield an error-weighted average value of 5·74 ± 0·04‰ (2SE, 95% confidence limit). Laser ablation multicollector inductively coupled plasma mass spectrometry results yield initial ɛHf (Zrn) values ranging from –2·0 to + 11·2 and an error-weighted average value of + 4·2 ± 0·2. We explore the apparent decoupling of O- and Hf-isotope systems through a variety of mass-balance mixing and assimilation–fractional crystallization models involving depleted- and enriched-mantle sources mixed with supra-crustal contributions. We find that the best fit to our isotope data involves mixing between an enriched, mantle-like source and up to 15% subducted, metasedimentary material. These results together with the homogeneity of δ 18 O (Zrn) values, the high-Sr/Y signature, and the mafic character of Western Fiordland Orthogneiss magmas indicate that the Cretaceous flare-up was triggered by partial melting and hybridization of subducted oceanic crust and enriched subcontinental lithospheric mantle. We argue that the driving mechanism for the terminal magmatic surge was the propagation of a discontinuous slab tear beneath the arc, or a ridge–trench collision event, at c. 136–128 Ma. Our results from the Early Cretaceous Zealandia arc contrast with the strong crustal signatures that characterize high-flux magmatic events in most shallow to mid-crustal, circum-Pacific orogenic belts in the North and South American Cordillera and the Australia Tasmanides; instead, our results document the rapid addition of new lower arc crust in <<15 Myr with lower crustal growth rates averaging 40–50 km 3  Ma −1  arc-km −1 from 128 to 114 Ma, and peaking at 150–210 km 3  Ma arc-km −1 from 118 to 114 Ma when ∼70% of the arc root was emplaced. Our results highlight the significant role of Cordilleran arc flare-up events in the rapid, net generation of continental crust through time.